Mobility and transport policy in Germany and France: Time for change and... joint solutions? - Laurent Guihéry; Julia Jarass (Cities and metropolises in France and Germany, 2022)
This chapter is devoted to mobility in France and Germany. First, key mobility indicators for the two countries are presented. This shows that private motorised transport still dominates in both France and Germany. Despite many negative effects on the climate, but also on health and quality of life, no far-reaching measures have been adopted. Hopes are pinned on technological progress and the integration of electromobility. However, this will not solve the shortage of land in cities or the car-dependence of many (low-income) households in rural areas in France. Subsequently, an empirical example from Berlin is used to show how financial and time restrictions affect the willingness of car drivers to switch to alternative modes of transport. Financial measures have a greater influence than time-related measures. For the French example, regional disparities and social dependence on the car are considered more closely. Finally, the current policy initiatives of the two countries are presented in order to assess the potentials of the transport transition.
urn:nbn:de:0156-1119074; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Mobility patterns in France and Germany; active mobility; scenarios for modal shift; sustainable development; social impacts